DNAJB3 Deficiency Exacerbates Diet-Induced Obesity and Insulin Resistance. (7th June 2021) - Nejat, Shadi; Scoggin, Shane; Menikdiwela, Kalhara; Moustaid-Moussa, Naima; Efotte, Aliyah; Dehbi, Mohammed
Abstract: Objectives: The prevalence of obesity and Type 2 Diabetes (T2D) continues to rise worldwide, leading to many other chronic diseases and imposing a large economic burden. DNAJ, also known as HSP40 (Heat Shock Protein-40), subfamily B, member 3 (DNAJB3), is a chaperone protein that can be induced under various stressors. Recent reports implicated DNAJB3 in protection against obesity and T2D. Specifically, DNAJB3 was downregulated in some patients with obesity and T2D; however, precise underlying mechanisms remained unclear. We hypothesized that lack of DNAJB3 will increase body weight and body fat, inflammation, glucose intolerance and insulin resistance in diet-induced obese mice, compared to B6 wild type (WT) littermates fed the same diets. Methods: Three DNAJB3 knockout (KO) mutant lines were generated at the Pennington Biomedical Research Center (KO 30, 44 and 47). Male and female KO and wild type (WT) littermates were fed a high fat diet (45% kcal fat) for 12 weeks. Body weight and composition were measured weekly, and a glucose tolerance test (GTT) was conducted. Following euthanasia, blood, adipose and muscle tissues were harvested and used for serum analyses and tissue gene/protein expression, respectively. Results: Compared to WT, only DNAJB3 KO male and female mice of line 47 demonstrated significantly higher body weight and fat mass ( P  < 0.05). Similarly, line 47 also showed a lower rate of glucose clearance as measured by GTT. Consistent with increased body weight and fat mass, male mice in line 47 also exhibited significantly higher mRNA levels of inflammatory markers including TNFα and IL-1β, in gonadal fat, compared to WT and lines 30 and 44. Moreover, similar trends towards increased TNF-α and MCP-1 expression was observed in muscle tissues of KO males of line 47, when compared to WT ( P  < 0.47), and line 30 ( P  < 0.15) respectively. Conclusions: Absence of DNAJB3, increases adiposity, glucose intolerance and inflammation in diet-induced obese mice in both males and females. these findings suggest that DNAJB3 plays an important role in metabolic functions and glucose homeostasis, which warrants further research as a potential therapeutic target for obesity and T2D. Funding Sources: Funded by Qatar National Research Funds, Hamad Bin Khalifa University & Qatar Biomedical Research Institute, Qatar.